Stability of ordered L12 and B2 precipitates in face centered cubic based high entropy alloys - Al0.3CoFeCrNi and Al0.3CuFeCrNi2. (October 2016) - Gwalani, B.; Soni, V.; Choudhuri, D.; Lee, M.; Hwang, J.Y.; Nam, S.J.; Ryu, H.; Hong, S.H.; Banerjee, R.
Abstract: Adding a small amount of Al to the well-known high entropy alloy (HEA), Al0.1 CoCrFeNi, to form Al0.3 CoCrFeNi, leads to the precipitation of highly refined ordered L12 precipitates, which are stable at 550 °C. However, the L12 precipitates (stoichiometry of (Ni, Cr)3 (Al, Fe, Co)) are de-stabilized and replaced by coarser B2 precipitates on annealing at 700 °C. Contrastingly, in the Co-free, Al0.3 CuCrFeNi2 high entropy alloy, the L12 precipitates are stable at both 550 °C ( 5 nm) and 700 °C ( 50 nm), and exhibit a stoichiometry of (Ni, Cu)3 (Al, Fe, Cr). These results lead to interesting insights into the stability of ordered phases in HEAs as a function of composition and temperature. Graphical abstract: